CORRELATION BETWEEN VISCERAL FAT LEVEL, BODY FAT PERCENTAGE AND BODY MASS INDEX WITH TOTAL CHOLESTEROL WOMEN IN MADIUN REGENCY - Widhi, Binar Wahyuning; Putri, Mega Arianti (Journal of Nursing Care and Biomoleculer, 2020)
Introduction: Hypercholesterolemia is one of risk factor that cause cardiovascular disease and the main cause of morbidity and mortality in the world. Obesity  often be related as one of predisposing factor in hypercholesterolemia. However, measuring obesity indicator is still different in many case. This study aim to understand the relation between visceral fat level, body fat percentage and body mass index with total cholesterol women in Madiun Regency. Method: Study design used is cross sectional and conducted 38 women (60-74 years) with purposive sampling technic. Data analysis technique used is Spearman correlations with ?=0,05. Result and analysis: visceral fat level and total cholesterol has the p value 0,005 and coefficient correlation 0,448. Its means that there is relationship between visceral fat level and total cholesterol with moderate correlation. Discussion: The increase of visceral fat related to the metabolic risk factor because it cause abnormalities lipoprotein metabolism that cause aterogenic dislipdemia. There are some factor can affected visceral fat deposit, one of them is age factor. Age factor can increasing visceral fat throught increasing lipoprotein-lipoid metabolism in plasma glucose in woman premenopause than younger women (Pascot et al, 1999). So it is very important to keep visceral fat level in normal level all the time.